To find the association between Vitamin D Deficiency and Pain intensity in Patients with Low Back Pain: An Observational Study - Yadav, Archana; Raya, Pawan Kumar (Birat Journal of Health Sciences, 2025)
Introduction: The aim of this observational study was to explore the association between Vitamin D deficiency and pain intensity in patients with low back pain. Vitamin D is known for its role in bone health, but recent studies have suggested its involvement in pain modulation and musculoskeletal disorders.Methods: This cross-sectional study was conducted from September 2024 and December 2024 in a Nepal Police Hospital (NPH), Kathmandu, Nepal at pain and orthopedic opd after receiving the approval from the ethical committee. Serum 25-hydroxyvitamin D (25(OH)D) level, Visual Analogue Scale (VAS), age, education level, marital status, working status, and body mass index (BMI) values was recorded. The limit value of Vitamin D was accepted as 20 ng/mL. Patients were divided into two groups according to their levels of Vitamin D. Patients with serum 25(OH)D levels below 20 ng/mL were considered as the deficiency of Vitamin D (Group 1) and patients with 20 ng/mL and over 20 ng/mL values were considered as normal in terms of Vitamin D (Group 2). Statistical analyses were performed to determine the prevalence of Vitamin D deficiency and low back pain and to explore potential associations.Results: Among the 216 participants, 61.46% were found to have Vitamin D deficiency (serum 25(OH)D < 20 ng/mL).  vitamin D level was 15.89 ± 4.06 ng/mL in group 1 as compared to mean vitamin D level of 28.03 ± 7.66 ng/mL in Group 2 which was statistically significantly (P < 0.0001).Conclusion: This study provides evidence suggesting a potential association between Vitamin D deficiency and higher pain intensity in patients with low back pain.